Discussion on the Construction and Improvement of the Rural Social Security System - Li, Quan (IJRDO - Journal of Business Management, 2016)
With the adjustment of the industrial structure and the continuous improvement of the integration of urban and rural areas in China, the improvement and reform of the rural social security system is more urgent. Based on this background, this paper analyzes the importance and necessity of improving the rural social security system, explores the problems existing in the rural social security system, and puts forward some suggestions to improve the rural social security system.